Evaluation of Epidemiologic Factors, Radiographic Features, and Pathologic Findings for Predicting Peritumoral Brain Edema in Meningiomas. Issue 1 (10th January 2020) - Sapkota, Mani R.; Yang, Zonghe; Zhu, Dan; Zhang, Yan; Yuan, Tengfei; Gao, Junfeng; Si, Tongguo; Wang, Junping
Abstract : Background: Despite several treatment options that are available for meningiomas, surgery is the only method currently practiced. Peritumoral brain edema (PTBE) in meningiomas causes difficulty marginalizing the dissection in an intraoperative setting. Purpose: To evaluate whether the epidemiological variables, imaging characteristics, and pathologic parameters are correlated with the presence of PTBE in meningiomas. Study Type: Retrospective study from 2015 to 2018. Subjects: In all, 550 patients with histopathologically confirmed meningioma were included. After exclusion of patients with extradural, spinal, and intraventricular meningiomas and those with image artifacts, a total of 441 patients were included in the final analysis. Field Strength/Sequence: Images were performed with 3T MR scanners and axial/sagittal T1 WI, axial/coronal T2 WI and axial/sagittal/coronal contrast‐enhanced T1 WI after administration of 0.1 mmol/kg of body weight of Gd‐DTPA. Assessment: Fourteen variables were patients' age, sex, skull changes, calcification, density, location, margin, volume, cerebrospinal fluid (CSF) cleft, signal intensity (SI) on T2 WI, degree and pattern of contrast enhancement, WHO histological classification, and Ki‐67 labeling index. Statistical Tests: The relationship between each factor and the formation of PTBE was examined by multivariate logistic regression analysis. Results: After multivariate logistic regression, the absence of CSF cleft (odds ratio [OR]: 63.43, 95% confidence interval [CI]: 27.24–121.42, P = 1.2 × 10 −8 ), non‐skull base location (OR: 15.32, 95% CI: 5.81–28.23, P = 0.0008), high SI on T2 WI (OR: 5.05, 95% CI: 2.27–14.88, P = 0.01), and G I uncommon subtypes (OR: 4.75, 95% CI: 1.42–15.94, P = 0.01) were found to be significant independent factors associated with the occurrence of PTBE in meningiomas. In patients with PTBE‐positive meningiomas, there was no significant correlation between the volume of PTBE and the volume of the tumor ( r = 0.17, P = 0.60). Data Conclusion: These factors may be suggestive of anticipating the formation of PTBE. Level of Evidence: 3 Technical Efficacy Stage: 3 J. Magn. Reson. Imaging 2020;52:174–182.